Ancylostomiasis in cats in Yogyakarta, Indonesia, and its causative genetic relations - JUNI CLAUDIA DAMI; LUH PUTU EKA DAMAYANTI; SOEDARMANTO INDARJULIANTO; DWI PRIYOWIDODO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Dami JC, Damayanti LPE, Indarjulianto S, Priyowidodo D. 2023. Ancylostomiasis in cats in Yogyakarta, Indonesia, and its causative genetic relations. Biodiversitas 24: 2605-2611. Ancylostomiasis is a zoonotic cat disease caused by one or more species of Ancylostoma spp. This study aims to determine ancylostomiasis in cats in Yogyakarta and its causative genetic relations. This research used ten cats with ancylostomiasis, based on the findings of Ancylostoma spp. eggs in their feces. Cats were examined clinically and laboratory, including blood profile and identification of Ancylostoma spp. eggs. The ITS1-5.8S-ITS2 region of Ancylostoma spp. was amplified by polymerase chain reaction (PCR) and sequenced; the results were compared with the Basic Local Alignment Search Tool (BLAST). As a result, physical examination showed that cats with ancylostomiasis suffered from diarrhea (100%), decreased appetite (70%), weakness (60%), anemia (60%), emaciation, and dull hair (10%). Blood examination showed that 5 (50%) cats had normochromic normocytic anemia, and 1 (10%) cat had hypochromic microcytic anemia. PCR tests, sequencing, and phylogenetic tests found that Ancylostoma spp. isolates had been successfully identified as Ancylostoma braziliense De Faria 1910, identical to A. braziliense from Australian isolate (DQ359149.1). Therefore, it was concluded that ancylostomiasis in cats in Yogyakarta was caused by A. braziliense.